ISLAMOLOGI TERAPAN SEBAGAI GERBANG ANALOG PENGEMBANGAN ISLAMIC STUDIES: Kajian Eksploratif Pemikiran Mohammed Arkoun - Baedhowi, B (IAIN Tulungagung, 2017)
Applied Islamology is a Mohammed Arkounâs thought and the critical notion of the weaknesses of Islamology. The weakness of Islamology because of its study of Islam and Islamic discourse is textual, ahistorical and only moves Islamic studies from certain texts and certain figures that are considered to represent,without relating to various phenomena of Islam and religious social reality,so that it reduces and forgets various elements, such as oral culture, unwritten experiences, both spoken and discourse or unspoken. Applied Islamology as an analogue of Islamic studies can also be explored, developed and will become an important Islamic study when it is always associated with various religious phenomena and social realities in society. Therefore, the dialectical relationship between the textual factor (language) - History and Islamic Studies is a unity and linkage in Islamic studies. Their absence of dialectical relationships will lead to gaps in both methodological and epistemological plots in the praxis of Islamic studies. This dialectical relationship that the writer wants to emphasize in studying Islamic studies. I think this dialectical relationship is the dynamics of the substance and function of religious studies with the existing Islamic discourse from time to time. In such a context, various social, methodological theories that are in line with our locality are indispensable for understanding the existing empirical social and religious realities. In this âintroductionâ paper, the writer will examine the dynamics of the dialectical relations of these three domains for the development of Islamic studies.